2018
DOI: 10.1177/0165551518761012
|View full text |Cite
|
Sign up to set email alerts
|

Predicting event mentions based on a semantic analysis of microblogs for inter-region relationships

Abstract: An ability to predict people’s interests in different regions would be valuable to many applications including marketing and policymaking. We posit that social media plays an important role in capturing collective user interests in different regions and their dynamics over time and across regions. Event mentions in microblogs of social media like Twitter not only reflect the people’s interests in different regions but also affect the posting of future messages as the content of microblogs propagates to others … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Some researchers have focused on analyzing twitter data using SNA metrics and similarity-based algorithms. For instance, the work in [36] analyzed event mentions in microblogs of social media, like twitter, for quantify-ing user's interests using similarity-based region network. Regional user interests are obtained for each topic by applying latent Dirichlet allocation to region-specific collections of tweets, and then compute pairwise similarities among regions.…”
Section: Other Approachesmentioning
confidence: 99%
“…Some researchers have focused on analyzing twitter data using SNA metrics and similarity-based algorithms. For instance, the work in [36] analyzed event mentions in microblogs of social media, like twitter, for quantify-ing user's interests using similarity-based region network. Regional user interests are obtained for each topic by applying latent Dirichlet allocation to region-specific collections of tweets, and then compute pairwise similarities among regions.…”
Section: Other Approachesmentioning
confidence: 99%
“…To put it simply, just like when Taobao is usually opened, the system will present the products you may need to buy on the main page without any input from the customer. Relevant studies have shown that after using the e-commerce personalized recommendation system, the sales of goods can be increased by 2% to 8% [10].…”
Section: Functionmentioning
confidence: 99%
“…analysed event mentions in microblogs of social media, like Twitter, in order to quantify users' interests using a similarity-based regional network [38].…”
Section: Similarity-based Approachesmentioning
confidence: 99%